Knowledge and awareness of glaucoma in Mexican patients with and without glaucoma diagnosis in an Ophthalmology Referral Center - Valeria Becerril-Ledezma; Daniela Alvarez-Ascencio; Clarisa Esther del Hierro-Gutiérrez; Alejandra Hernandez-Oteyza; Jesús Jiménez-Román (International Journal of Ophthalmology, 2022)
AIM: To assess and compare knowledge and awareness of glaucoma in subjects with and without glaucoma diagnosis attending an Ophthalmology Referral Center. METHODS: This cross-sectional study was conducted at Asociación Para Evitar la Ceguera in Mexico City, using a questionnaire formulated by a group of experts following the Delphi panel rules, and pre-tested in a pilot study. The questionnaire was applied and compared between: glaucoma patients, relatives of glaucoma patients and patients without glaucoma. Socio-demographic data was collected to assess correlation with the level of knowledge using Logistic regression models, estimating the odds ratios (OR), 95% confidence intervals, and P<0.05. RESULTS: Three hundred and ninety-four subjects were enrolled; with a median age of 61y. One hundred and thirty-four (34%) were patients with glaucoma, 152 (38.6%) patients without glaucoma, and 108 (27.4%) relatives of patients with glaucoma. Two hundred and ninety-one (73.9%) participants were aware of the term “glaucoma”. Regarding knowledge 46.7% had moderate knowledge, 37.8% had poor knowledge, and 15.5% good knowledge. Overall, relatives of glaucoma patients had the highest scores, and patients without glaucoma got the lowest scores. A positive correlation was found between better knowledge and frequent ophthalmological examinations OR 2.24 (P=0.02), higher education level OR 4.17 (P=0.00) and having a family member with glaucoma OR 3.28 (P=0.00). CONCLUSION: Awareness and knowledge of glaucoma in subjects attending an Ophthalmology Referral Center is predominantly moderate or poor. This has important implications regarding attitudes that can result in lack of follow up in ophthalmological care.